Polanyi in the Pilbara - Peck, Jamie (Australian Geographer, 2013)
This paper outlines a ‘substantivist’ approach to the regional economy of the Pilbara in Western Australia, inspired by a constructive reinterpretation of Karl Polanyi's methodological legacy. Beyond the metaphor of embeddedness, it makes the case for a more wide-ranging methodological engagement with Polanyi's brand of substantivist socioeconomics, in dialogue with the empirical investigation of actually existing and variegated socioeconomic formations. A Polanyian optic, amongst other things, calls attention to enduring sources of heterogeneity in this distinctive regional-economic formation, even under the hegemonies extractive capitalism and neoliberal developmentalism.
Geography
Keywords: Aboriginal economies; economic geography; mining; the Pilbara

Turning Financial Markets inside Out: Polanyi, Performativity and Disembeddedness - Muellerleile, Chris (Environment and Planning A, 2013)
In light of the spread of markets across the globe and deeper into daily life, this paper argues for a more robust analysis and application of Karl Polanyi's conception of (dis)embedded markets coupled with the performativity thesis authored mainly by Michel Callon. It suggests that while disembeddedness as a concept is necessary for an analysis of contemporary financial markets that are increasingly self-referential, it is not sufficient. Despite the suggestion of a gulf between Polanyian and Callonian economics, there are important similarities in the two frameworks. The similarities are considered along with the considerable difference, all in an attempt to develop a more robust methodological framework for analyzing financial markets. Performativity, it is argued, can help fill the gaps in Polanyi's embeddedness framework, albeit only when that concept's tendency to produce aspatial and apolitical arguments are taken seriously. The paper uses an abbreviated case study of the development of US financial derivative markets in the 1970s and 1980s to argue that markets must be considered in light of both their institutional and geographic entanglements as well as their (dis)embeddedness in systems of calculativeness and mathematical modeling. Specifically the paper analyzes the tension between the derivative origin story authored by Donald MacKenzie, which focuses on neoclassical pricing models like the Black—Scholes—Merton option pricing formula, and my own empirical research, which suggests the urban-economic geography of Chicago played a key role in the development of these instruments.
Geography
Keywords: Black—Scholes; CALLON; Michel; Chicago; disembeddedness; economic geography; embeddedness; financial derivatives; markets; performativity; urban geography

Disembedding Polanyi: Exploring Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
The paper provides an introduction to a theme issue devoted to the influence—and the potential—of the work of Karl Polanyi in the field of economic geography. Polanyi has been an inspirational figure in the heterodox field of ‘socioeconomics’, where the inseparability of the economic and the social is taken to be axiomatic. He has also made recurrent appearances in economic geography since the early 1990s, as a progenitor of the ‘networks and embeddedness’ approach and in his role as a prescient critic of market fundamentalism. But the potential of Polanyian approaches in economic geography has only been fitfully explored. In this context, the contributions to this theme issue make the case for a more sustained—but also open, critical, and creative—engagement with Polanyi's legacy.
Geography
Keywords: economic geography; embeddedness

For Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
Karl Polanyi has been an influential but also somewhat elusive figure in economic geography. Best known for his evocative notion of social embeddedness, it is perhaps fitting that Polanyi's presence has been more metaphorical than substantive. The paper asks what a more engaged Polanyian economic geography might look like. Focusing on methodological affinities, a response is developed in terms of a commitment to the substantivist (as opposed to formal) analysis of actually existing economic formations, together with a more purposive embrace of institutionalism, holism, and comparativism.
Geography
Keywords: comparative economy; economic geography; institutionalism; substantivism

Living without Fruit Flies: Biosecuring Horticulture and its Markets - Phillips, Catherine (Environment and Planning A, 2013)
In this paper, informed by more-than-human and biosecurity literatures, I attend a neglected nonhuman considered a serious agricultural pest: the fruit fly. In addressing what it takes to live without fruit flies, biosecurity is theorised as ongoing, enacted achievement sustained (or not) by everyday and eventful interactions of heterogeneous spaces, strategies, and participants—human and nonhuman. Relations of fruits, flies, and people are explored through one vital attempt to biosecure life: Australia's Fruit Fly Exclusion Zone (FFEZ), a tristate pest-free area established to protect commercial horticulture from the fruit fly. Fruit flies become problematised as their appetites and mobilities confound fruit production and marketing, and affiliated biosecurity controls. Making fruit safe enrolls policy and agricultural sectors, but also more dispersed agents (travellers, residents, trees) and management sites (primarily off-farm). Since its introduction, the FFEZ's ongoing biosecuring normalised, with only occasional outbreak events. However, recent unprecedented outbreaks evoke questions about the FFEZ's future status. In such eventful times, it is worth reflecting on what kinds of living are possible in biosecurity zones—for flies, for resident human communities, and for agrifood networks.
Geography
Keywords: Australia; Queensland fruit fly; agriculture; biosecurity; more-than-human

Men and Things: Karl Polanyi, Primitive Accumulation, and Their Relevance to a Radical Green Political Economy - Prudham, Scott (Environment and Planning A, 2013)
Now is an important moment to be thinking and talking about a critical and normative green political economy. Whether via attempts to develop effective and socially just climate policies at multiple scales of governance [including REDD (reducing emissions from deforestation and degradation) schemes], or to develop proliferating and controversial neoliberal instruments for dealing with undesirable environmental change, environmental governance, and environmental change in the context of contemporary global capitalism are on the agenda. What would a critical and normative green political economy for the current moment look like? This paper draws on Karl Polanyi's The Great Transformation as a resource for answering that question. In particular, Polanyi's discussion of problematic and dualistic notions of nature and society in early political economy and the role he accords social struggles over land in developing his theory of fictitious commodities, embeddedness and the double movement are revisited. The paper stresses how Polanyi's ideas, at once conceptual and polemical, draw centrally on Marx's theorization of primitive accumulation as an inherent, ‘extra-economic’ facet of historical—geographical capitalism, a differentiated unity linking the commodification and objectification of human and nonhuman natures as exchange-values. In this respect, Polanyi offers (or seems to offer) a potential reconciliation of a politics of nonhuman and human nature through his emphasis on primitive accumulation as a site of both political struggle and epistemic transformation.
Geography
Keywords: Karl Polanyi; economism; green political economy; primitive accumulation

Institutional Mobility and Mutation in the Global Capitalist System: A Neo-Polanyian Analysis of a Transnational Cotton Standards War, 1870–1945 - Quark, Amy A. (Environment and Planning A, 2013)
This paper explores the dynamics of institutional change in periods of instability in the global capitalist system. Two recent bodies of literature—actor-centered institutionalism and the ‘policy mobilities’ approach—emphasize how contextual and historical specificities drive transformation as institutions move across space. However, scholars in both traditions give less attention to the systematic patterns of social conflict that influence how policies move and mutate. Drawing on the case of a standards war in the global cotton trade from 1870 to 1945, I build on these literatures by linking them to a neo-Polanyian theory of social conflict within periods of market-led development. From this view, we must understand institutions, their mobilities, and mutations as constituted by and constitutive of struggles over how the global capitalist system should be organized and in whose interests. This requires building on, but also deepening Polanyi's analysis. While Polanyi emphasized the destructive effects of liberal market projects that generate social conflict, the ‘push-backs’ against liberal market projects are more diverse than Polanyi suggested, and social conflict can also emerge out of the creative moments of liberal market expansion.
Geography; History
Keywords: cotton; double movement; history; interfirm competition; interstate competition; market expansion; standards

Marketization beyond Neoliberalization: A Neo-Polanyian Perspective on China's Transition to a Market Economy - Zhang, Jun (Environment and Planning A, 2013)
This paper proposes a neo-Polanyian framework of neoliberalization-as-marketization for understanding geohistorically embedded marketization based on five interlinked theoretical conceptualizations: embedded marketization, hybrid integration, double movement, active society, and qualitative state. I argue that this framework can be useful to supplement existing theorizing of neoliberalism, and to facilitate comparative case studies across vastly differently contexts. This framework is then taken to analyze China's post-Mao transition to a market economy. I argue that China's gradualist transition from a centrally planned economy to a mixed economy has been maneuvered by a self-regulating party-state (dis)embedded in a deactivated (active) society. Due to the existence of multiple veto players and intraparty ‘double movement’, the marketization was able to be mostly socially progressive until 1993. However, it was no longer the case when the ‘socialist market economy’ was enshrined and, without political liberalization, the Chinese version of neoliberalization has become even bleaker than elsewhere.
Geography
Keywords: China; double movement; marketization; neo-Polanyian; neoliberalization

The boundaries of cosmopolitanism: Karl Polanyi and the 'Magyar-Jewish mongrel' - Dale, Gareth (Environment & Planning A, 2013)
The author offers his opinion on Hungarian historian Karl Polanyi and the views Karl expressed in a series of letters he sent to his brother Michael Polanyi. In these letters Karl wrote about the Germans attitude towards other Jews and the developing volatile social environment in Budapest, Hungary at the beginning of the 20th Century. He also wrote on the animosity between the Germans and the Jews.
Geography
Keywords: Baltic States; Germans; Jews; POLANYI; Michael; 1891-1976; biography; cosmopolitanism; history; social development

Polanyian pedagogies in planning and economic geography - Rankin, Katharine N. (Environment & Planning A, 2013)
The author offers his opinion on social economic planning and the educational courses available on them. The author states that planning social economy was a part of Hungarian economist Karl Polanyi's policy in early 20th century to stabilize the economic conductions in Hungary at that time. The auditor says that Polanyi's book "the Great transformation" formed the basis. which if acted upon, would have preevented the Global Financial Crisis of 2008.
Geography
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; central economic planning; global financial crisis; 2008-2009; nonprofit sector

Class and situated knowledge in Polanyi's The Great Transformation - Schoenberger, Erica (Environment & Planning A, 2013)
The author offers his views on a controversial fundraising organized by then U.S. Presidential Candidate Mitt Romney in May 2012 where he commented that he won't be bothered about a section of society who only have access to national income but have not contributions or income tax to give. The author cites this as one the reason why Romney was not successful and states that Hungarian Economists Karl Polanyi's socioeconomics theory is relevant in the 21st century.
Geography
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; ROMNEY; Mitt; 1947-; income tax; national income; political fundraising; socioeconomics; voters

Polanyi, double movements, and political economic transformations - Smith, Adrian (Environment & Planning A, 2013)
The author offers his opinion on Hungarian Economist Karl Polanyi's opinion on social economy. The auth through use of recent events such as the Arab Uprising since 2011 and the post communism societies discusses Polanyi's views with those of political economic planners. The author states that social change within a society post the economic recession could have been avoided had Polanyi's views being taken seriously.
Geography
Keywords: Arab Spring Uprisings; 2011-; Arab countries; POLANYI; Karl; 1886-1964; double movement; history; nonprofit sector; political economic analysis; postcommunist societies; social change

The two Karls, or reflections on Karl Polanyi's The Great Transformation - Walker, Richard (Environment & Planning A, 2013)
The article reviews the book "The Great Transformation," by Karl Polanyi.
Geography
Keywords: Great Transformation; The (Book); book review; nonfiction; socioeconomics

A variety of capitalism … with Chinese characteristics? - Peck, Jamie; Zhang, Jun (Journal of Economic Geography, 2013)
The ‘varieties of capitalism’ framework represents an influential methodological innovation in the field of comparative political economy. It seeks to account for enduring spatial variations in national economic performance by recourse to macroinstitutional analysis, drawing ideal-type distinctions between liberal market economies, modeled on USA, and coordinated market economies, modeled on Germany. Moving beyond critiques of varieties literature—for instance, its methodological nationalism; its preoccupation with limited, formal registers of (national) institutional variety; its growing reliance on rational-choice, firm-centric methods; its failure to account for the pronounced interpenetration and mutual dependence of capitalist economies and its tendency to privilege typological elaboration over causal explanation—this article explores the critical (counter?) case of Chinese capitalism. It considers the extent to which the Chinese economy can be meaningfully characterized as capitalist; the character of its state form and recent development path and its position within—or beyond—conventional understandings of capitalist variety.
Geography
Keywords: China; Chinese capitalism; capitalism; developmental state; economic structure; economic systems; free enterprise; socialist state; variegated capitalism; varieties of capitalism

On Life as a Fictitious Commodity: Cities and the Biopolitics of Late Neoliberalism - Rossi, Ugo (International Journal of Urban & Regional Research, 2013)
Building on a biopolitical understanding of the economic crisis, this essay contends that the occurrence of the crisis warns that life is not a real commodity but - to put it in Karl Polanyi's terms - a 'fictitious commodity'. This means that life cannot be integrally subsumed within the economy, and therefore the crisis is to be seen as a pathological way in which societies react to the pervasiveness of capitalist relations, showing the illusory character of self-regulating markets and ownership ideologies. Two mutually contradictory biopolitical responses to the neoliberal crisis, led by the state and grassroots movements respectively, are discussed in the concluding section of the essay.
Geography; Urban Studies
Keywords: biopolitics; biopolitics (sociobiology); capitalism; consumers; crisis; fictitious commodities; global financial crisis; 2008-2009; government regulation; home ownership; housing; late neoliberalism; neoliberalism; urban economics

Towards the Great Transformation: (5) Materialisms, old and new: theory, sources, and praxis (an introduction) - Catterall, Bob (City, 2013)
One of the major critical claims of this series is that the social and socio-spatial sciences, in their currently dominant form, cannot, for lack of a de-familiarising agenda, one that leads to an appropriate and continually tested strategy (praxis), effectively counter the normalized and naturalized forms and processes of late capitalist urbanization, normalized by mainstream theory in the service of established power, and their extrapolation into a ‘planetary future’. Critical urban theory presents/presented a step forward but it is losing some critical momentum and thus purchase on present and future realities in its neglect of aspects of its own intellectual heritage, of ‘extra-scientific’ resources including the cognitive aspect of the arts/humanities and ordinary experience (‘the university of the streets’), and in its too restrictive theoretical, spatial and temporal foundations.1 It thus, to a significant extent, fails to give an adequate account, a representational and ethical/normative accounting, of ‘the great transformation’ of marketisation/capitalism as told and analysed notably by Polanyi and Marx, and to the possibilities of and its relationship to praxis for a post-marketised/capitalist great transformation. We need a purposeful reading of the full range of the lived materialities of the planet (not just abstracted away into a distinctly immaterial usage of the notion of the ‘planetary’ and, indeed, of ‘urbanization’). We need in fact a sensuous materialism, an old but still unrealized project. This, the first of two futher episodes, is a brief retrospective and prospective survey, drawing on earlier work in this series and sketching in future directions, of such a materialism (materialisms, old and new): theory, sources and praxis.
Geography
Keywords: capitalism; cities & towns; cultural studies; de-familiarisation; marketisation; marketization; materialism; monsters; urban community development; urbanization